ANALYSIS OF PEER EDITING TECHNIQUE TO IMPROVE WRITING ENGLISH - Jimmi Jimmi; Fika Hafidziah (Yayasan Akrab Pekanbaru, 2018)
The objective of this research is to know the effectiveness of Peer Editing technique to improve writing English. Teaching writing is the productive skill learnt by the students. The research was conducted at the first grade students at SMP N 24 Tangerang in academic year 2017/2018. This research focuses on analyzing of peer editing technique to improve writing English. This research is using descriptive qualitative method. As a result the writer is found that: (1) peer editing technique helps the students to increase their abilities on writing skill (2) the students understand more about how to be a writer and peer editor (3) the students not only doing peer review but also doing their own introspection.